Task Based Learning Approach to Foster EFL Learners’ Listening and Speaking Skills (2020)
ABSTRACT: This action research project analyzed how the implementation of Task-Based Learning Approach (TBL) fostered students’ listening and speaking skills since students did not have opportunities for practicing these skills in previous years. The participants were 35 eighth-grade students from a public institution in El Carmen de Viboral. Data collection instruments included observations, journals, a survey, students’ artifacts, a focus group interview and a questionnaire, whose analysis was done through processes of assembling, coding, and comparing data to building meanings and interpretations (Burns, 2010). As results, the data demonstrated that students improved listening and speaking skills thanks to pre-task activities. Nevertheless, the main task and language focus activities did not contribute to the main objective of the study due to unmanageable changes.